2018
DOI: 10.1590/1413-81232018233.05982016
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake among adolescent students and association with social capital and socioeconomic status

Abstract: Alcohol intake among adolescent students and association with social capital and socioeconomic status

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…As a result, people in the outgroup receive unfair treatment. In the study of the social determinants of drinking behavior, the existing literature focuses on two areas: social pressure [10,11] and socioeconomic status [12,13]. When facing social discrimination, people often relieve the pressure by consuming alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, people in the outgroup receive unfair treatment. In the study of the social determinants of drinking behavior, the existing literature focuses on two areas: social pressure [10,11] and socioeconomic status [12,13]. When facing social discrimination, people often relieve the pressure by consuming alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…A dysfunctional family dynamic, with frequent discussions between the adolescents and their parents, lack of dialogue, and parents’ lack of participation in their children's daily activities enhances exposure to risk situations 31 , such as alcohol consumption. Several studies show that having a family member who uses any kind of drug (legal or illegal) influences its consumption by adolescents 7 , 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The earlier the consumption, the greater the risk of adolescents becoming excessive consumers throughout life 7 , 8 . Moreover, early consumption increases the risk of exposure to sexually transmitted infections, traffic accidents, personality disorders, poor school performance, aggressive behavior, and unintentional injuries 9 11 .…”
Section: Introductionmentioning
confidence: 99%
“…According to Fuligni (2019), numerous studies have shown the social, psychological, and health benefits of fulfilling the human need to make social contributions. Behaviors that involve giving to others, ranging from volunteering to providing instrumental or social assistance, have been linked to healthy psychological, behavioral, and physical profiles, including lower morbidity, fewer health problems, reduced daily stress, and lower depression rates (e.g., Ballard et al, 2019; Jorge et al, 2018). An additional study on Brazilian adolescents found that a greater level of social capital (measured by their involvement in volunteer activities) was associated with a significantly lower risk of binge drinking (Cívico‐Ariza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%